Beneficial effects of seaweed-derived components on metabolic syndrome via gut microbiota modulation - Zang, Liqing; Baharlooeian, Maedeh; Terasawa, Masahiro; Shimada, Yasuhito; Nishimura, Norihiro (Frontiers in Nutrition, 2023)
Metabolic syndrome comprises a group of conditions that collectively increase the risk of abdominal obesity, diabetes, atherosclerosis, cardiovascular diseases, and cancer. Gut microbiota is involved in the pathogenesis of metabolic syndrome, and microbial diversity and function are strongly affected by diet. In recent years, epidemiological evidence has shown that the dietary intake of seaweed can prevent metabolic syndrome via gut microbiota modulation. In this review, we summarize the current in vivo studies that have reported the prevention and treatment of metabolic syndrome via seaweed-derived components by regulating the gut microbiota and the production of short-chain fatty acids. Among the surveyed related articles, animal studies revealed that these bioactive components mainly modulate the gut microbiota by reversing the Firmicutes/Bacteroidetes ratio, increasing the relative abundance of beneficial bacteria, such as Bacteroides, Akkermansia, Lactobacillus, or decreasing the abundance of harmful bacteria, such as Lachnospiraceae, Desulfovibrio, Lachnoclostridium. The regulated microbiota is thought to affect host health by improving gut barrier functions, reducing LPS-induced inflammation or oxidative stress, and increasing bile acid production. Furthermore, these compounds increase the production of short-chain fatty acids and influence glucose and lipid metabolism. Thus, the interaction between the gut microbiota and seaweed-derived bioactive components plays a critical regulatory role in human health, and these compounds have the potential to be used for drug development. However, further animal studies and human clinical trials are required to confirm the functional roles and mechanisms of these components in balancing the gut microbiota and managing host health.